The Effect Of Muhadatsah Score On Student’s Self Confidence In Speaking Arabic - Fitri Zakiyah; Ahmad Dani (Ijaz Arabi Journal of Arabic Learning, 2023)
This article aims to describe the implementation of muhadatsah in the Arabic learning process and its effect on students’ self-confidence in speaking Arabic at the Islamic junior high school al Manar Yogyakarta, Indonesia. The researchers applied mixed qualitative and quantitative approaches. They used observation, interviews, documentation, and questionnaire to collect the data from 16 students. And then analyze them qualitatively and quantitatively. The findings of this study indicate that the implementation of muhadatsah in this school does not work effectively. The score of muhadatsah is good enough but does not relate to students’ self-confidence in speaking Arabic, which is at a low rate. The teacher carries out the learning evaluation process in written tests, so measuring students’ speaking ability is not appropriate. The teacher faced difficulties applying muhadatsah in the learning and teaching process. The diversity of students’ cognitive, the lack of supervision and language discipline from school, the lack of awareness of speaking Arabic among students, and online learning during the pandemic become challenges faced in applying muhadatsah as a method and additional course effectively. The researchers provide some recommendations to school administrators to resolve these academic problems by optimizing the implementation of muhadatsah, designing strict rules and interactive activities, and conducting the speaking test in the oral examination for an appropriate evaluation process.